Prevalence and Risk Factors of Acute Ischemic Stroke in Patients with Antiphospholipid Syndrome: A Retrospective Monocenter Analysis - Paschalis Evangelidis; Nikolaos Kotsiou; Panagiotis Kalmoukos; Zacharo Ntova; Theodosia Papadopoulou; Sofia Chissan; Anastasia Sarvani; Styliani Kokoris; Elisavet Grouzi; Michael Doumas; Sofia Vakalopoulou; Eleni Gavriilaki (Journal of Cardiovascular Development and Disease)
(1) Background: Antiphospholipid syndrome (APS) is associated with thrombotic events and the laboratory identification of antiphospholipid antibodies (aPL), in which lupus anticoagulant (LA), anticardiolipin (aCL), and anti-β2 glycoprotein I antibodies are included. The aim of the current retrospective study is to examine clinical characteristics and risk factors of ischemic stroke as a clinical manifestation of APS. (2) Methods: Adult patients diagnosed with APS between 1 January 2009 and 1 June 2024 were retrospectively enrolled in this study. Sydney-revised Sapporo criteria were used for the diagnosis of APS, while ischemic stroke was diagnosed based on the acute onset of focal neurologic deficits and confirmed with radiological findings. (3) Results: We studied 115 patients with APS. Specifically, 28 (24.35%) patients, with a mean age (standard deviation) of 54 (±12.5), had ischemic stroke as a clinical manifestation of APS. In univariate analysis, stroke development was associated with the following factors: age (p < 0.001), livedo reticularis (p = 0.046), avascular necrosis (AVN) (p = 0.046), hypertension (p < 0.001), dyslipidemia (p = 0.013), aCL IgG (U/L) antibodies title (p = 0.035), and adjusted global APS score (aGAPSS) (p = 0.047), while in multivariate analysis, it was associated with age (p = 0.006), hypertension (p < 0.001), AVN (p = 0.006), livedo reticularis (p = 0.035), aCL IgG title (p = 0.004), and aGAPSS (p = 0.002). (4) Conclusions: Stroke is a common initial manifestation of APS, with cardiovascular risk factors, particularly hypertension, being highly prevalent.